Improved AlScN/GaN heterostructures grown by metal-organic chemical vapor deposition. (22nd January 2021) - Manz, Christian; Leone, Stefano; Kirste, Lutz; Ligl, Jana; Frei, Kathrin; Fuchs, Theodor; Prescher, Mario; Waltereit, Patrick; Verheijen, Marcel A; Graff, Andreas; Simon-Najasek, Michél; Altmann, Frank; et al.
Abstract: AlScN/GaN epitaxial heterostructures have raised much interest in recent years, because of the high potential of such structures for high-frequency and high-power electronic applications. Compared to conventional AlGaN/GaN heterostructures, the high spontaneous and piezoelectric polarization of AlScN can yield to a five-time increase in sheet carrier density of the two-dimensional electron gas formed at the AlScN/GaN heterointerface. Very promising radio-frequency device performance has been shown on samples deposited by molecular beam epitaxy. Recently, AlScN/GaN heterostructures have been demonstrated, which were processed by the more industrial compatible growth method metal-organic chemical vapor deposition (MOCVD). In this work, SiN x passivated MOCVD-grown AlScN/GaN heterostructures with improved structural quality have been developed. Analytical transmission electron microscopy, secondary ion mass spectrometry and high-resolution x-ray diffraction analysis indicate the presence of undefined interfaces between the epitaxial layers and an uneven distribution of Al and Sc in the AlScN layer. However, AlScN-based high-electron-mobility transistors (HEMT) have been fabricated and compared with AlN/GaN HEMTs. The device characteristics of the AlScN-based HEMT are promising, showing a transconductance close to 500 mS mm −1 and a drain current above 1700 mA mm −1 .